Field evaluation of two types of EDS-integrated PV modules with different configurations and surface properties. (15th July 2022) - Javed, Wasim; Khoo, Yong Sheng; Figgis, Benjamin; Guo, Bing
Highlights: EDS with thinner dielectric layer has higher soiling mitigation efficiency. EDS soiling mitigation is more efficient in dry and windy weather conditions. Surface with greater hydrophobicity has higher soiling rate. Durability of thin-glass EDS needs improvement. Abstract: In this study, two prototypes of PV modules with integrated electrodynamic dust shield (EDS) were characterized in the lab and tested in the field to determine their effectiveness in soiling mitigation. The surface properties of the prototype modules' front cover were measured to evaluate their effects on the EDS dust removal performance. The soiling of each EDS-PV module was assessed based on its PV power output, from which the EDS cleaning efficiency was quantified in field conditions during winter and summer periods. The dust removal efficiency of glass-surface EDS-PV modules was approximately 30%, about three times higher than that of polymer-surface modules. The EDS technology cleaned more effectively in dry and windy weather conditions. The EDS modules' front surfaces varied significantly with respect to thickness, hydrophobicity, and the electrostatic potential pattern, contributing to the variation of the EDS efficiency of modules. The EDS-PV module with a hydrophobic polymer surface had a higher soiling rate and lower cleaning efficiency than a thinner, hydrophilic glass surface. The results of this study may help improve design and manufacturing methods for more efficient and robust EDS devices integrated into PV modules.